Multiplicador del gasto público y su relación con la producción agregada de Loreto periodo 2017 – 2021 - Zumaeta Lagunas, Piero Jefrey (2023)
The thesis focused on verifying whether there exists a multiplier effect of public spending that is related to the aggregate production of the Loreto region, using the period from 2017 to 2021 as the temporal analysis interval. To achieve this, a linear econometric model is proposed where the study variables are linearized using the log transformation in order to properly link their scales. The results indicated that there is a positive multiplier effect of total public spending on the aggregate production of the region, with a value of 0.44 percent. However, when analyzing separately the effect of spending executed by the national, regional, and local governments, it was found that only the public spending executed by the national government generated a statistically significant positive multiplier effect on the aggregate production of the region, while the spending executed by the regional and local governments did not have a significant effect. These results are important because they highlight the relevance of public spending at the national level, and suggest that spending allocation should be carefully considered to maximize its impact on the economy of Loreto.